New EU rules relating to the consumer withdrawal in distance contracts on financial services and through online interfaces - Miranda Serrano, Luis María (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Directive (EU) 2023/2673 of the European Parliament and of the Council, of 22 November 2023, has been drafted with the dual purpose of addressing the many challenges arising from the digitisation of financial markets and simplifying European consumer law. Its publication has led to the repeal of the previous legislation on the subject (Directive 2002/65/EC) and the incorporation into Directive 2011/83/EU (on consumer rights) of new rules aimed at regulating, on the one hand, the special features of consumer contracts on financial services concluded at a distance and, on the other, the right of withdrawal in any contracts concluded through online interfaces, whether or not they relate to financial services. This paper provides the key elements of the new legal regime of the consumer’s right of withdrawal as it results from this new maximum harmonisation Directive.